Towards a phonological typology of Uralic languages - Pajusalu, Karl; Uiboaed, Kristel; Pomozi, Péter; Németh, Endre; Fehér, Tibor (Eesti ja soome-ugri keeleteaduse ajakiri. Journal of Estonian and Finno-Ugric Linguistics, 2018)
The paper focuses on phonological similarities between Uralic languages. The study is based on a dataset which includes 33 word-prosodic and segmental features of 28 Uralic languages or main dialects, including all traditional subgroups of the language family. In statistical analysis clustering and dimension reduction techniques such as multidimensional scaling are applied. This methodology enables to explore distinctive subgroups of languages as well as calculate distances between languages and language groups. As a result we present a quantitative phonological typology. The main division appears between western and central-eastern phonological types of the Uralic languages. The detected phonological subgroups coincide with the traditional ones, i.e. Finnic, Saami, Mordvin, Mari, Permic, Hungarian, Ob-Ugric and Samoyedic. The Hungarian subgroup (Standard Hungarian, Csángó Hungarian) and the Ob-Ugric subgroup (Northern Mansi, Eastern Mansi, Northern Khanty, Eastern Khanty) are internally stable. However, their interrelation and relationship with other groups is ambiguous; according to our results, Hungarian is typologically closer to the Western Uralic language groups (i.e. Finnic and Saami), whereas Ob-Ugric languages form a distinct branch of Central-Eastern Uralic. In general, the results reveal a significant influence of multiple areal connections on the phonological formation of Uralic languages.Аннотация. Карл Паюсалу, Кристел Уйбоаэд, Петер Помози, Эндре Немет и Тибор Фехер: К фонологической типологии уральских языков. В статье рассматриваются фонологические сходства между уральскими языками. Исследование основывается на выборке данных, которая включает 33 просодических и сегментных признака, которые применяются к 28 уральским языкам или их основным диалектам. Эта выборка покрывает все традиционно выделяемые группы уральской семьи. Для статистической обработки данных используются методы кластерного анализа и многомерного шкалирования. Такой подход позволяет исследовать выявленные подгруппы языков и рассчитывать расстояния между языками и языковыми группами. Результатом анализа является квантитативная фонологическая типология. Основная граница разделяет западный и центрально-восточный типы уральских языков. Выявленные фонологические подгруппы языков совпадают с традиционными: прибалтийско-финская, саамская, мордовская, марийская, пермская, венгерская, обско-угорская и самодийская. Венгерская подгруппа (стандартный венгерский и чангошский диалект) и обско-угорская подгруппа (северный мансийский, восточный мансийский, северный хантыйский, восточный хантыйский) демонстрируют внутреннюю стабильность. Однако их собственные взаимоотношения и отношение к другим подгруппам неоднозначны: наши результаты показывают, что венгерский язык типологически ближе к западно-уральской группе (т. е. прибалтийско-финским и саамским языкам), тогда как обско-угорские языки оказываются четко выделяемой ветвью центрально-восточных уральских языков. В целом, результаты раскрывают существенное влияние разнообразных ареальных связей на становление фонологии уральских языков.Ключевые слова: уральские языки, прауральский язык, фонология, типология, просодия слова, лингвистические ареалыKokkuvõte. Karl Pajusalu, Kristel Uiboaed, Péter Pomozi, Endre Németh ja Tibor Fehér: Uurali keelte fonoloogilisest tüpoloogiast. Artikkel keskendub uurali keelte fonoloogiliste sarnasuste võrdlemisele. Analüüsitav andmestik hõlmab 33 sõnaprosoodilist ja segmentaalset tunnusjoont 28-st uurali keelest või põhimurdest, mille hulgas on keeli kõigist traditsioonilistest allrühmadest. Statistilises uuringus rakendatakse klasteranalüüsi ja multidimensionaalsest skaleerimist. Nii eristatakse olulised allrühmad ja arvutatakse kaugused keelte ja keelerühmade vahel, saades uurali keelte kvantitatiivse fonoloogilise tüpoloogia. Esmane lahknemine ilmneb geograafiliselt läänepoolsete ning kesk- ja idapoolsete uurali keelte vahel. Nende sees tulevad esile traditsioonilised allrühmad: läänemeresoome, saami, mordva, mari, permi, ungari, obiugri ja samojeedi. Ungari (ungari kirjakeel, csángó) ja obiugri (põhjamansi, idamansi, põhjahandi, idahandi) on sisemiselt stabiilsed, kuid suhe nende kahe rühma vahel on ambivalentne. Meie tulemuste põhjal on ungari tüpoloogiliselt lähedasem läänepoolsetele uurali keeltele (st läänemeresoomele ja saamile), obiugri keeled moodustavad aga eraldi allrühma kesk- ja idauurali keelte hulgas. Saadud tulemused näitavad areaalsete kontaktide tähtsust uurali keelte fonoloogilise eripära kujunemises.Märksõnad: uurali keeled, proto-uurali, fonoloogia, tüpoloogia, sõna prosoodia, keeleareaalid